Dampak Dualisme Kepemimpinan Sinode GPKB Terhadap Pelayanan Pendeta SE-Distrik V Humbang - Lastiur Batubara; Megawati Manullang; Nurelni Limbong; Haposan Silalahi; Hanna Dewi Aritonang (Jurnal Mahasiswa Kreatif, 2023)
The aim of this research is to determine the impact of the dualism of GPKB synod leadership on the ministry of pastors in District V Humbang. The research method used is qualitative research. The data collection technique for this research is using semi-structured interviews and documentation in the form of images. Based on the results of research conducted by the author, the impact of dualism in leadership on the ministry of pastors in Humbang V District causes emotional pain or disappointment and makes it difficult to reach a point of peace between pastors. The dualism of leadership experienced by pastors and congregations is a bad influence on both pastors' services, where daily needs or salaries are unable to cover life's necessities, but this is triggered by commotion or misunderstanding between pastors which burdens the congregation and pastors. The impact of dual leadership in GPKB in Humbang District V includes sirang paradatan, moving churches, building new churches and so on. The impact of this dualism in leadership becomes an obstacle to the pastor's ministry because of disappointment in the hearts of the congregation. This problem has become an obstacle in the ministry of pastors in the V Humbang district, healing the emotional wounds of the congregation and the disappointment of the congregation, even though the pastor's salary or daily needs are not necessarily met, the pastor's loyalty to continuing to serve at GPKB never gives up because the spirit of service within the pastor is more important than status because what they do is shepherd, not be the government over the life of the congregation.